Implementation Of Property Rights Limitation Provisions In Community Life In Bantul District Special Region Of Yogyakarta - Prihati Yuniarlin; Endang Heriyani (Journal Of Social Science (JoSS), 2022)
Property rights are material rights that are absolute. Based on Article 570 of the Criminal Code, property rights are rights that are fully and freely used, however, the freedom to use property rights is not unlimited, but there are limitations. The problem in this research is: How is the application of the provisions on the limitation on the use of property rights in social life in Bantul Regency, DIY? The results showed that the application of restrictions on the use of property rights in people's lives in Bantul Regency can be seen in the Yogyakarta State Administrative Court Decision Number 04/G/2013/PTUN.YK which was corroborated by the Surabaya State Administrative High Court Decision Number: 149/B/ 2013/PT. TUN. SBY. The decision was declared null and void and revoked the Decree of the Head of the Bantul Regency Licensing Service Number: 3497/DP/001/XI/2012 concerning Disturbance Permits for "HIKMAH" Chicken Livestock Business at the location of Dusun Mangir Lor RT.03, Sendangsari Village, Pajangan District, District Bantul, because it contradicts Article 5 paragraph (4) of Bantul Regency Regional Regulation Number 6 of 2011 concerning Nuisance Permits, and the Decree of the Governor of the Special Region of Yogyakarta Number 176 of 2003 concerning Standard Levels of Vibration, Noise and Odor in the Province of the Special Region of Yogyakarta and the Principles General Good governance especially the principle of accuracy. With the cancellation of the Nuisance Permit, the owner of a broiler farm business is no longer allowed to continue his livestock business, meaning that the owner cannot use his property in the form of a cage on his private land for a chicken farm business. So the use of this property is not free without limits, but there are limitations